Calcium-suppressed Technique in Dual-layer Detector Computed Tomography to Evaluate Knee Articular Cartilage - Meng, Qinglin; Liu, Mengqi; Deng, Weiwei; Chen, Ke; Wang, Botao; Zhang, Xiaohuan; Chen, Zhiye (Current Medical Imaging, 2021)
Background: Calcium-suppressed (CaSupp) technique involving spectral-based images has been used to observe bone marrow edema by removing calcium components from the image. Objective: This study aimed to evaluate the knee articular cartilage using the CaSupp technique in dual-layer detector computed tomography (DLCT). Methods: Twenty-eight healthy participants and two patients with osteoarthritis were enrolled, who underwent DLCT and magnetic resonance imaging (MRI) examination. CaSupp images were reconstructed from spectral-based images using a calcium suppression algorithm and were overlaid with conventional CT images for visual evaluation. The morphology of the knee cartilage was evaluated, and the thickness of the articular cartilage was measured on sagittal proton density-weighted and CaSupp images in the patellofemoral compartment. Results: No abnormal signal or density, cartilage defect, and subjacent bone ulceration were observed in the lateral and medial femorotibial compartments and the patellofemoral compartment on MRI images and CaSupp images for the 48 normal knee joints. CaSupp images could clearly identify cartilage thinning, defect, subjacent bone marrow edema, and edema of the infrapatellar fat pad in the same way as MRI images in the three knee joints with osteoarthritis. A significant difference was found in the mean thickness of the patellar cartilage between MRI images and CaSupp images, while the femoral cartilage presented no significant difference in thickness between MRI images and CaSupp images in all 48 knee joints. Conclusion: The present study demonstrated that CaSupp images could effectively be used to perform the visual and quantitative assessment of knee cartilage.
Keywords: calcium-suppressed technique